Gradual deterioration of fatty liver disease to liver cancer via inhibition of AMPK signaling pathways involved in energy-dependent disorders, cellular aging, and chronic inflammation - Meng, Sha-Sha; Gu, Hong-Wei; Zhang, Ting; Li, Yu-Sang; Tang, He-Bin (Frontiers in Oncology, 2023)
Introduction Hepatocellular carcinoma (HCC) is the most prevalent primary liver cancer kind. According to recent research, a fatty liver increases the risk of hepatocellular cancer. Nevertheless, the AMPK signaling pathway is crucial. In addition, 5’-AMP-activated protein kinase (AMPK) is strongly linked to alterations in the tumor microenvironment, such as inflammation, hypoxia, and aging. The objective of this study is to evaluate the impact of the AMPK signaling pathway on the progression of fatty liver to HCC. Methods In this study, we established a mouse liver cancer model using high-fat diets and nano-nitrosamines (nano-DEN). In addition, we employed a transcriptomic technique to identify all mRNAs detected in liver samples at the 25th weekexpression of proteins linked with the LKB1-AMPK-mTOR signaling pathway, inflammation, aging, and hypoxia was studied in microarrays of liver cancer tissues from mice and humans. These proteins included p-AMPK, LKB1, mTOR, COX-2, β-catenin, HMGB1, p16, and HIF-1α. Results Data were collected at different times in the liver as well as in cancerous and paracancerous regions and analyzed by a multispectral imaging system. The results showed that most of the genes in the AMPK signaling pathway were downregulated. Prakk1 expression was upregulated compared to control group but downregulated in the cancerous regions compared to the paracancerous regions. Stk11 expression was downregulated in the cancerous regions. Mtor expression was upregulated in the cancerous regions. During liver cancer formation, deletion of LKB1 in the LKB1-AMPK-mTOR signaling pathway reduces phosphorylation of AMPK. It contributed to the upregulation of mTOR, which further led to the upregulation of HIF1α. In addition, the expression of β-catenin, COX-2, and HMGB1 were upregulated, as well as the expression of p16 was downregulated. Discussion These findings suggest that changes in the AMPK signaling pathway exacerbate the deterioration of disrupted energy metabolism, chronic inflammation, hypoxia, and cellular aging in the tumor microenvironment, promoting the development of fatty liver into liver cancer.